MENTAL HEALTH OF NURSING PROFESSIONALS IN FRONT OF ACTION IN COVID 19 - Correia da Costa, Ayra; da Silva Lopes , Maria Helena; Elis de Carvalho Sanino , Giane (Health and Society, 2023)
The new coronavirus pandemic began in December 2019 in the city of Wuhan in China, resulting in several deaths and leaving several people with sequelae. Health professionals, being on the front lines, were one of the most affected, with the constant witnessing of deaths, dealing with a tiring, exhausting workday and the lack of resources in hospitals to provide assistance to patients. The research aimed to assess whether there was emotional exhaustion in nursing professionals in the face of Covid-19. The method used was descriptive and exploratory quantitative field research, carried out through data collection through a form in google forms sent by social networks. Being the inclusion criteria: nursing professionals, technicians and assistants who reside in São Paulo and who work with patients with Covid-19, and as exclusion criteria: professionals who do not work in the health area and nor nursing professionals who have not worked with patients with covid-19 or who do not reside in São Paulo. After data collection, relative frequency/percentage calculations were performed, showing the number of professionals who have mental fatigue due to the pandemic. The calculated results were presented in graphs and tables. The research results showed that 75% (mean C 4.6 to ˃ 5.0) of nursing professionals have very intense stress and 25% (2.1 to 3.5) have mild to moderate stress. Therefore, it was evidenced that there is emotional exhaustion in nursing professionals who work or have worked with users of health services affected by Covid-19, with a very intense level of stress and mild to moderate stress, not failing to show an absence of stress.